Acceso a la información : hacia la democratización de la administración pública - Ferreyra, Leandro Eduardo (2013)
The work is structured in three sections. In the first one, the intention is to\ndelineate the concept of the right of access to public information and the complexities\nderived from it following what was resolved and legislated in different systems. In the\nsecond one, the Argentinean normative structure and its deficits are analyzed. In the\nthird section and based on the initial reflections, final considerations and suggestions\nare developed.